L’impatto del Covid-19 sugli ordinamenti giuridici delle Chiese cristiane protestanti: Prime note - Valenzi, Ilaria (Salute umana e tradizioni religiose di fronte alle emergenze sanitarie, 2021)
Starting from the reconstruction of the main models of the legal systems of the Protestant churches, the contribution intends to describe the reaction that some of these churches operating in Italy have implemented in the face of the pandemic emergency. In a situation of exceptionality, the essential elements of those legal systems have revealed their resilience to a greater or lesser extent, depending on the degree of juridization of the churches. Even some theological principles of central relevance have been tested, with solutions still open.